Role of engineering technologist to solve the impact of COVID-19 to the society - Karthigesu, Nagarajoo; Chong, Wai Wai; Chooi, Shir Ley; Akasha, Azeera Hanim (2020)
The aim of this work is to study on the impact of COVID-19 to society and the role of engineering technologists to resolve the issue. Coronavirus disease (COVID-19) is an irresistible infection induced by a newly discovered coronavirus. The virus disseminated immediately from a person when a COVID-19 case coughs or exhales producing droplet that reaches the nose, mouth or eyes of another person. The outbreak of coronavirus is a front and leading a human buskin affecting hundreds of thousands of people. This disease also becomes a severe growing impact on society, the global economy, and education. This paper will discuss the impact of COVID-19 on society. Social reciprocities, interactions, and relations between the people have become united into our life. COVID 19 had changed the daily behavior of humans and the surrounding ecological system. So, if such an interaction is absent leads to stressful states of isolation, anxiety, panic, mental disorders, health hazards, and many other issues that impact the life of the person and the cooperative society as a whole. This paper also dedicated to presenting the role of engineering technologist with a perspective on the evolving situation and implications for the world. The technologist should come up with a design solution that would give guidance to solve the Impact of COVID-19 on the Society. They need to find out the solution to relative well in tackling the virus. Technologist can help share rightful knowledge and information that can help with COVID-19 responses. Technologist’ response to the virus has been providing information, research, and assistance that will have an immeasurable impact on the pace and efficiency of our response to the COVID-19. The outbreak is going fast, and some of the perspectives in this paper may fall rapidly out of date. However, the data analysis of COVID-19 in the world will be given in this paper.